How to Develop a Project-Based Learning (PBL) Model on the Batobo Tradition - Hendri Marhadi; Sapriya Sapriya; Kama Abdul Hakam; Dasim Budimansyah (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2022)
Learning models appearing in the classroom are psychologically far from students’ daily lives, despite the fact that there are numerous traditions available to students that might form the basis for the development of a learning model. This study was intended to produce a model of Project Based Learning (PBL) based on Batobo. The Batobo tradition performed by Kuantan Singingi people in Riau is a tradition of working together on an agricultural land. This study used research and development (R&D) proposed by Borg and Gall stages to develop the tradition based learning model. The data collection technique started from conducting a literature review, interviewing groups or community leaders and designing models. The results of the research revealed that Batobo based Project Based Learning model was conducted in five stages in learning included the initiation (manyamulo), followed by project planning (mancangkul/manugal), project implementation (mananam), discussion (manuai) and the last stage was evaluation (closing). The Batobo based Project Based Learning model described the learning activities carried out by referring to the Batobo tradition. Based on the results of the study, it can be concluded that the PBL model based on the batobo tradition which consists of five stages of learning developed is suitable for use in elementary schools.